Socioeconomic status and self-rated health in China: Findings from a cross-sectional study. Issue 12 (March 2019) - Yu, Tong; Jiang, Yan; Gamber, Michelle; Ali, Gholam; Xu, Tan; Sun, Wenjie
Abstract : Abstract: To investigate whether socioeconomic status is associated with the self-rated health (SRH) status among Chinese. A cross sectional study including a national sample was conducted among Chinese adults in 2008. In total, 3225 participants were selected by a multistage cluster sampling method. Both general self-rated health and time-comparative self-rated health were measured by a standardized questionnaire. Logistic regression models were used to estimate the odds ratios (ORs) (95% confidence intervals, CIs) of occupation with SRH by occupation, and adjusted for age, sex, education, area, marriage, smoking, drinking, and health status. Overall, 34.4% of study participants reported "good" on the general SRH (male: 35.8%; female: 32.9%) and 26.2% reported "good" on the time-comparative SRH (male: 27.2%; female: 25.3%). The prevalence of "good" general SRH varied from 28.8% to 52.8% and the prevalence of time-comparative SHR varied from 21.7% to 33.9% in different occupations. The adjusted OR (Odd Ratio) for "good" on the general SRH was 1.35 (95% CI: 1.20–1.52) for the occupation of civil servants, 2.23 (95% CI: 1.96–2.54) for farmers, and 1.15 (95%CI: 1.01–1.31) for businessmen. The full adjusted OR of "good" on the time-comparative SRH was 1.36 (95% CI: 1.17–1.58) for students and was 1.25 (95% CI: 1.10–1.42) for civil servants. In presented study, 34.4% of the participants reported "good" on the general SRH, and 26.2% participants reported "good" on the time-comparative SRH. The prevalence of "good" general SRH and "good" time-comparative SRH varied among occupations.